2006
DOI: 10.1002/gcc.20323
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic genomic imbalances in pediatric pheochromocytoma

Abstract: Pheochromocytoma (PCC) in children is rare, genetically not well described, and often related to a poor prognosis. We detected genomic imbalances in all 14 tumors from children analyzed by comparative genomic hybridization. A combinatorial loss of chromatin from 3p and 11p was a common feature in 10 of 14 (72%) patients, which was a result of either a loss of a total chromosome 3 and a total chromosome 11 in 6 of 10 patients, or confined deletions of their p arms in 4 of 10 patients. All patients exhibiting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…In agreement with other studies [4,[19][20][21][22], we found unbalanced chromosomal aberrations in PCCs, using CGH. This suggests that chromosomal changes might be an important tumorigenic event.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In agreement with other studies [4,[19][20][21][22], we found unbalanced chromosomal aberrations in PCCs, using CGH. This suggests that chromosomal changes might be an important tumorigenic event.…”
Section: Discussionsupporting
confidence: 94%
“…progenetix.net/progenetix/;14.9. 2009) showed high concordance of the aberration pattern [19][20][21].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This pattern of loss has been previously mentioned in PCC from VHL patients, but has so far not been related to a subgroup of sporadic PCC (Lui et al 2002, Hering et al 2006. In order to exclude that this subgroup represented occult VHL disease, we performed mutation analysis of the entire VHL coding region, in which we could not detect germline mutations.…”
Section: Discussionmentioning
confidence: 73%
“…VHL-related PCC, however, show distinct genetic aberrations consisting of loss of chromosomes 3 and 11 (Lui et al 2002, Hering et al 2006.…”
Section: Introductionmentioning
confidence: 99%